Comparative phylogenetics of repetitive elements in a diverse order of flowering plants (Brassicales). Issue 7 (16th May 2021) - Beric, Aleksandra; Mabry, Makenzie E; Harkess, Alex E; Brose, Julia; Schranz, M Eric; Conant, Gavin C; Edger, Patrick P; Meyers, Blake C; Pires, J Chris
Abstract: Genome sizes of plants have long piqued the interest of researchers due to the vast differences among organisms. However, the mechanisms that drive size differences have yet to be fully understood. Two important contributing factors to genome size are expansions of repetitive elements, such as transposable elements (TEs), and whole-genome duplications (WGD). Although studies have found correlations between genome size and both TE abundance and polyploidy, these studies typically test for these patterns within a genus or species. The plant order Brassicales provides an excellent system to further test if genome size evolution patterns are consistent across larger time scales, as there are numerous WGDs. This order is also home to one of the smallest plant genomes, Arabidopsis thaliana— chosen as the model plant system for this reason—as well as to species with very large genomes. With new methods that allow for TE characterization from low-coverage genome shotgun data and 71 taxa across the Brassicales, we confirm the correlation between genome size and TE content, however, we are unable to reconstruct phylogenetic relationships and do not detect any shift in TE abundance associated with WGD.